Tetrahydrofuran-based amino acids as library scaffolds. - Edwards, A; Ichihara, O; Murfin, S; Wilkes, R; Whittaker, M; Watkin, D; Fleet, G (2004)
A furanose sugar amino acid (SAA) has been utilized as a library scaffold for the first time. Two furanose SAA scaffolds were examined to illustrate their potential for derivatization. The resulting 99-member library contained three orthogonal points of diversification that allowed easy access to ethers and carbamates from a hydroxyl moiety, a range of ureas from an azide (via an amine), and a range of amides from a methyl ester. The novel amide formation (by displacement of the methoxide from the methyl ester moiety) was achieved in good yield and purity with high structural confidence. Full characterization of several library intermediates (including a crystal structure) was obtained. The library was submitted for antibacterial screening.